A Breakthrough in Sustainable Production of Formate Salts: Combined Catalytic Methanol Dehydrogenation and Bicarbonate Hydrogenation. Issue 12 (26th September 2014) - Joó, Ferenc
<x xml:space="preserve">Abstract</x> G'day, formate! The recent breakthrough discovery by Beller et al. in the production of formate salts by combined dehydrogenation of methanol and hydrogenation of bicarbonates is discussed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>